2021
DOI: 10.3390/cancers13112663
|View full text |Cite
|
Sign up to set email alerts
|

Immune System-Related Changes in Preclinical GL261 Glioblastoma under TMZ Treatment: Explaining MRSI-Based Nosological Imaging Findings with RT-PCR Analyses

Abstract: Glioblastomas (GB) are brain tumours with poor prognosis even after aggressive therapy. Previous work suggests that magnetic resonance spectroscopic imaging (MRSI) could act as a biomarker of efficient immune system attack onto GB, presenting oscillatory changes. Glioma-associated microglia/macrophages (GAMs) constitute the most abundant non-tumour cell type within the GB and can be polarised into anti-tumour (M1) or pro-tumour (M2) phenotypes. One of the mechanisms to mediate immunosuppression in brain tumour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 96 publications
2
23
0
Order By: Relevance
“…Figure 1 summarizes those detected changes. Our results [ 43 , 56 ] show that in a fast-growing GL261 GB tumor before treatment, about 68% of the tissue volume is occupied by fast proliferating tumor cells (average 2900 Ki67+ cells/mm 2 ) and other non-tumor, non Iba1+ cell types, such as myeloid-derived suppressor cells (MDSC) [ 28 ]. The rest of the volume is mostly represented by innate Iba1+ IS cells (microglia/macrophages, 12%), lymphocytes (below 1%), and acellular spaces (also dubbed by other authors microcystic volume [ 58 ]) (19%).…”
Section: Hypothesis Proposalmentioning
confidence: 99%
See 3 more Smart Citations
“…Figure 1 summarizes those detected changes. Our results [ 43 , 56 ] show that in a fast-growing GL261 GB tumor before treatment, about 68% of the tissue volume is occupied by fast proliferating tumor cells (average 2900 Ki67+ cells/mm 2 ) and other non-tumor, non Iba1+ cell types, such as myeloid-derived suppressor cells (MDSC) [ 28 ]. The rest of the volume is mostly represented by innate Iba1+ IS cells (microglia/macrophages, 12%), lymphocytes (below 1%), and acellular spaces (also dubbed by other authors microcystic volume [ 58 ]) (19%).…”
Section: Hypothesis Proposalmentioning
confidence: 99%
“…Microglia/macrophages under different polarization statuses also have different metabolomic patterns [ 54 , 63 ]. In this respect, changes in the microglia/macrophage polarization (M1 vs. M2) have been described in both GB [ 64 , 65 , 66 , 67 ] and, more precisely, in GL261 GB [ 56 , 68 , 69 , 70 ]. Then, the composition of the cell types, their status and tissue architecture, and the changes upon treatment can together contribute to metabolome pattern changes that lead to measurable changes in the TRI ( Figure 1 B).…”
Section: Hypothesis Proposalmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that efferocytosis is closely related to the polarization of the M1/M2 phenotype. Unlike nonneoplastic diseases, the inflammatory defense function of macrophages/microglia can be inhibited in the glioma microenvironment, where they cells are changed from the M1 phenotype (proinflammatory) to the M2 phenotype (anti-inflammatory) ( Calero-Pérez et al, 2021 ). The mainstream view is that anti-inflammatory substances released after efferocytosis induce microglia to polarize to the M2 type.…”
Section: Nervous System Diseases Related To Efferocytosismentioning
confidence: 99%